Intake and digestibility of mix-herbal supplement blocks for Bali Cattle fed with agricultural by-product in Bengkulu, Indonesia - Dwatmadji.; Suteky, T.; Soetrisno, E.; Riyanda, D. W.; Yulianto, H.; Saragih. M. S. (International Journal of Agricultural Technology, 2020)
The result of the Mix-Herbal Supplement Blocks (MHSB) on Bali cattle showed that the initial live and final weights did not differ (p>0.05) among the treatments. However, the average daily gain on group SCL differs significantly (p<0.05) with the others. Bali cattle fed with S0, SCL, and SZO formulas gained 0.39, 1.25, and 0.79 kg day-1 respectively. MHSB did not significantly (p>0.05) affect intake and digestibility in all treatments. It might be concluded from this study that the amount of mix-herbal supplements could be given in a higher amount to the Bali cattle.